1371. Safety, Tolerability, and Pharmacokinetics of Multiple Doses of TP-6076, a Novel, Fully Synthetic Tetracycline, in a Phase 1 Study. (26th November 2018) - Tsai, Larry; Moore, Alison
Abstract: Background: TP-6076 is a novel, fully synthetic tetracycline being developed for the treatment of serious bacterial infections, including those caused by multidrug-resistant Acinetobacter baumannii . TP-6076 has demonstrated potent activity in vitro against carbapenem-resistant strains of A. baumannii, with MIC90 64 times lower compared with tigecycline and 256 times lower compared with minocycline. We now report the results of a multiple ascending dose study in normal healthy volunteers. Methods: This was a phase 1, single-site, randomized, double-blind, placebo-controlled dose-escalating, multiple dose study in healthy adults who met the inclusion/exclusion criteria and provided informed consent prior to any study procedure. Cohorts of eight subjects each (six active and two placebo) received daily doses of 6.0 to 40.0 mg TP-6076 or placebo for 7 days. Plasma and urine samples for pharmacokinetic (PK) analyses were collected starting immediately prior to dosing until 96 hours after the last dose. Safety was assessed through collection of adverse events (AEs), clinical laboratories, vital signs, ECG, and physical examination data. Results: The geometric mean derived PK parameters for TP-6076 were: There were no serious or severe AEs reported. The most frequently reported AEs were gastrointestinal events, including nausea and vomiting, and localized infusion site reactions. There were no clinically significant changes in clinical laboratory values, ECG parameters, or physical examination findings. Conclusion: Following multiple IV doses of TP-6076, plasma exposure increased as dose increased. Multiple IV doses of TP-6076 were generally well tolerated, with higher gastrointestinal adverse event rates in the higher dose groups. Disclosures: L. Tsai, Tetraphase Pharmaceuticals: Employee and Shareholder, Salary. A. Moore, Tetraphase Pharmaceuticals: Employee, Salary.